2020
DOI: 10.3390/ijms21072462
|View full text |Cite
|
Sign up to set email alerts
|

MTA, an RNA m6A Methyltransferase, Enhances Drought Tolerance by Regulating the Development of Trichomes and Roots in Poplar

Abstract: N6-methyladenosine (m6A) is the most prevalent internal modification present in the mRNAs of all higher eukaryotes, where it is present within both coding and noncoding regions. In mammals, methylation requires the catalysis of a multicomponent m6A methyltransferase complex. Proposed biological functions for m6A modification include pre-mRNA splicing, RNA stability, cell fate regulation, and embryonic development. However, few studies have been conducted on m6A modification in trees. In particular, the regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…Populus methylome studies revealed that drought stress changed the DNA methylation level of TF coding genes and further altered their expression pattern ( Liang et al, 2014 ). An RNA m 6 A methyltransferase coding gene from poplar, MTA , was shown to enhance drought tolerance by promoting trichome and root development ( Lu et al, 2020 ). As mentioned above, several histone modification enzymes, such as AtHDA15 and PtrADA2b-PtrGCN5, were found to interact with key TFs, such as AtMYB96 and PtrAREB1-2, to regulate drought response in Arabidopsis and poplar ( Lee and Seo, 2019 ; Li et al, 2019 ).…”
Section: Epigenetic Regulation Of Drought Responsementioning
confidence: 99%
“…Populus methylome studies revealed that drought stress changed the DNA methylation level of TF coding genes and further altered their expression pattern ( Liang et al, 2014 ). An RNA m 6 A methyltransferase coding gene from poplar, MTA , was shown to enhance drought tolerance by promoting trichome and root development ( Lu et al, 2020 ). As mentioned above, several histone modification enzymes, such as AtHDA15 and PtrADA2b-PtrGCN5, were found to interact with key TFs, such as AtMYB96 and PtrAREB1-2, to regulate drought response in Arabidopsis and poplar ( Lee and Seo, 2019 ; Li et al, 2019 ).…”
Section: Epigenetic Regulation Of Drought Responsementioning
confidence: 99%
“…The function of m 6 A levels under heat stress has also been investigated in pak‐choi (Liu et al ., 2020). In poplar, PtrMTA overexpression plants have higher trichome density and a more developed root system (Lu et al ., 2020). However, current studies have primarily focused on the biological function of m 6 A methylases in response to abiotic stresses, but our understanding of their molecular mechanisms remains very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, epitranscriptome manipulation has great potential for improving crop traits. Recent studies revealed that harnessing m6A regulation could remarkably improve economically important traits in crops [ 16 , 132 , 135 ]. Transgenic expression of a human RNA demethylase FTO (fat mass and obesity associated) in rice and potato stimulates root meristem cell proliferation, tiller bud formation, promotes photosynthetic efficiency, and results in ~50% increases in yield and biomass.…”
Section: Epigenome and Epitranscriptome Engineering For Crop Improvementmentioning
confidence: 99%
“…Overexpression of PtrMTA encoding a component of the m6A methyltransferase complex that participated in the formation of m6A methylation exhibits enhanced poplar tolerance to drought stress. Poplar plants that overexpression of PtrMTA displayed an increased density of trichomes and a more developed root system than that of the wild type [ 135 ]. In strawberry, the overexpression of FveMTA or FveMTB , encoding m6A methyltransferases, accelerates fruit ripening, while the suppression of either delays fruit ripening, providing a good example of fruit maturity control through epitranscriptome manipulation [ 132 ].…”
Section: Epigenome and Epitranscriptome Engineering For Crop Improvementmentioning
confidence: 99%